Os resultados do pró – letramento na prática docente em duas escolas da rede pública do município de Santana - AP - CAVALCANTE, Alda Gomes (UNIFAP – Universidade Federal do Amapá, 2022)
This study investigates the outcome of the Pro-Literacy teaching in two schools of the Public municipality Santana. The research focuses on data generated in the course conducted by the MEC, in partnership with universities and institutions that comprise the National Network of Continuing Education, with the accession states and municipalities. To this end, we carried out a bibliographic review on the subject, which sought to verify the historical process of continuous education, public policy and its projection in the news, as well as a major component that handles the travel, that is, the Literacy. In order to consolidate the subject, an investigation was conducted in two schools with 10 teachers who attended the course, as with the qualitative method approach within a perspective of ethnographic analysis. By having the data analyzed, it was found that during the course of the program, there was a significant uptake by teachers, whereas after the course, the results obtained in the Pro-Literacy focused heavily on teacher's daily practice, confirming that this program called the mother tongue teaching in the early grades of the schools surveyed. The results also point to the need for a more articulated system of continuing education that does not have a compensatory character in relation to initial teacher training, but that will allow for a continuous space of reflection and knowledge construction in teacher professional context.